2008
DOI: 10.1345/aph.1k497
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence Following Coronary Artery Bypass Graft Surgery: Assessment of Beliefs and Attitudes

Abstract: In summary, patient beliefs and attitudes regarding medications, along with other social, economic, and demographic factors, help explain differences in self-reported adherence to standard drug therapy following CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 19 publications
6
31
0
Order By: Relevance
“…The authors concluded that P-OM3 should be added to currently employed secondary prevention measures because of its potential additive benefits. 42 Similar cost-benefits were found using comparable study methodologies applied to patients in Australia, Belgium, Canada, Germany, Poland, 43 and the United Kingdom. 44 In addition, investigators in the United States found that P-OM3 can be expected to reduce overall costs and improve outcomes when used for secondary prevention of cardiovascular disease.…”
Section: Maintaining Cardiovascular Health In Patients With Mixed Dyssupporting
confidence: 60%
See 1 more Smart Citation
“…The authors concluded that P-OM3 should be added to currently employed secondary prevention measures because of its potential additive benefits. 42 Similar cost-benefits were found using comparable study methodologies applied to patients in Australia, Belgium, Canada, Germany, Poland, 43 and the United Kingdom. 44 In addition, investigators in the United States found that P-OM3 can be expected to reduce overall costs and improve outcomes when used for secondary prevention of cardiovascular disease.…”
Section: Maintaining Cardiovascular Health In Patients With Mixed Dyssupporting
confidence: 60%
“…[38][39][40][41] Some patients rely on dietary supplements and trust the claims made about these products, yet they can be reluctant to believe the benefits of prescription drugs. 42 Nonadherence to statin therapy is a major problem. All medical professionals should strive to overcome the misconceptions and other factors that are common to medication nonadherence in general.…”
mentioning
confidence: 99%
“…A number of published studies covering a variety of clinical areas report that adherence to medication regimes is associated with beliefs about medicines [1,[20][21][22][23][24]. If, as their findings suggest, low adherence is associated with negative beliefs about medicines, one approach to improving adherence would be to apply an intervention that could modify those beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that patients with cardiovascular disease are known to adhere poorly to medication (29). Based on the findings of a qualitative research study, it was shown that patients perceived medicines as an "intrusion into their daily life", were concerned about having to take them for the rest of their lives, and that some patients disliked taking medicines (8).…”
Section: Taking Medications Multiple Timesmentioning
confidence: 99%